Home
/
Math
/
The rule to get from one term to the next in a sequence is x_(n+1)=3x_(n)+8 If x_(1)=4 work out the value of x_(3)

Question

The rule to get from one term to the next in a sequence is
x_(n+1)=3x_(n)+8
If x_(1)=4 work out the value of x_(3)

The rule to get from one term to the next in a sequence is x_(n+1)=3x_(n)+8 If x_(1)=4 work out the value of x_(3)

expert verifiedVerification of experts

Answer

4.7329 Voting
avatar
ElizabethVeteran · Tutor for 9 years

Answer

To begin with, for \( x _ { 2 } \):<br />\[<br />x _ { 2 } = 3 x _ { 1 } + 8 <br />= 3(4) + 8<br />= 20<br />\]<br /><br />Then for \( x _ { 3 } \):<br />\[<br />x _ { 3 } = 3 x _ { 2 } + 8<br /> = 3(20) + 8 <br /> = 68<br />\]<br />Therefore, the value of \( x_{3} \) equals 68.

Explain

## Step1: <br />Identify the recursive formula given in the problem which defines the steps to get from one term to another.<br />***The recursive formula here is:*** \(x _ { n + 1 } = 3 x _ { n } + 8\).<br /><br />## Step2:<br />From step1, we realize that to evaluate \(x _ { 3 } \), we have to calculate \( x_{2}\) first. Plug \( n = 1 \) (since given \( x_{1} \)) into the recursive formula.<br /><br />### The formula applied here for first calculation is \( x _ { 1+1 } = 3 x _ { 1 } + 8 \).<br /><br />## Step3:<br />Calculate based on this formula. Given that \( x_{1} = 4 \), substitute it into the above formula to find \( x_{2} \).<br />After obtaining \( x_{2} \), use this \( x_{2} \) to calculate \( x_{3} \).<br /><br />### The formula applied here for second calculation is\( x _ { 2+1 } = 3 x _ { 2 } + 8 \).<br /><br />By substitution using multiple steps, step-by-step, and performing the arithmetical operation, \( x _ { 3 } \) can be obtained.
Click to rate:

Hot Questions

More x